Gemigliptin: An Update of Its Clinical Use in the Management of Type 2 Diabetes Mellitus - Sung‐Ho Kim; Jung-hwa Yoo; Woo Je Lee; Cheol‐Young Park (2016)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are a new class of oral antidiabetic agent for the treatment of type 2 diabetes mellitus. They increase endogenous levels of incretin hormones, which stimulate glucose-dependent insulin secretion, decrease glucagon secretion, and contribute to reducing postprandial hyperglycemia. Although DPP-4 inhibitors have similar benefits, they can be differentiated in terms of their chemical structure, pharmacology, efficacy and safety profiles, and clinical considerations. Gemigliptin (brand name: Zemiglo), developed by LG Life Sciences, is a potent, selective, competitive, and long acting DPP-4 inhibitor. Various studies have shown that gemigliptin is an optimized DPP-4 inhibitor in terms of efficacy, safety, and patient compliance for treatment of type 2 diabetes mellitus. In this review, we summarize the characteristics of gemigliptin and discuss its potential benefits in clinical practice. Keywords: Diabetes mellitus, type 2; Dipeptidyl-peptidase IV inhibitors; LC15-0444